New record of the soft-bodied genus Franciscideres (Kinorhyncha) from Argentina, with notes on its movement and morphological variation - Rucci, Kevin A.; Neuhaus, Birger; Bulnes, Verónica N.; Cazzaniga, Néstor J. (Zootaxa, 2020)
Samples collected from Monte Hermoso, Buenos Aires Province, Argentina revealed the presence of specimens of the genus Franciscideres Dal Zotto et al., 2013, previously known only from Brazil. This morphotype seems to differ from the only known species, Franciscideres kalenesos Dal Zotto et al., 2013, in the following characters: (1) presence of ventrolateral tubes on segment 1, (2) introvert features, (3) each segment composed of a closed cuticular ring, (4) trunk cuticle ornamented by a secondary fringe of knob-like structures, (5) posterior margin of segment 10 ventrally terminating in two lateral and one broad triangular lobes, (6) posterior margin of segment 11 centrally terminating in four lobes (7) lateral terminal spines armed with thorn-like processes, (8) pores/sensory spots/gland cells distribution and (9) sexual dimorphism in segments 10 and 11. Because of the lack of full information about F. kalenesos from Brazil, we consider the new exemplars as Franciscideres cf. kalenesos. Additionally, we provide new information about the movement of this species using light microscopy and we compare these movements with those of other meiofaunal inhabitants.